GWAS of stool frequency provides insights into gastrointestinal motility and irritable bowel syndrome - Ferdinando Bonfiglio; Xingrong Liu; Christopher Smillie; Anita Pandit; Alexander Kurilshikov; Rodrigo Bacigalupe; Tenghao Zheng; Hieu Nim; Koldo Garcia-Etxebarria; Luis Bujanda; Anna Andreasson; Lars Agreus; et al. (Elsevier, 2021)
Summary: Gut dysmotility is associated with constipation, diarrhea, and functional gastrointestinal disorders like irritable bowel syndrome (IBS), although its molecular underpinnings are poorly characterized. We studied stool frequency (defined by the number of bowel movements per day, based on questionnaire data) as a proxy for gut motility in a GWAS meta-analysis including 167,875 individuals from UK Biobank and four smaller population-based cohorts. We identify 14 loci associated with stool frequency (p ≤ 5.0 × 10−8). Gene set and pathway analyses detected enrichment for genes involved in neurotransmitter/neuropeptide signaling and preferentially expressed in enteric motor neurons controlling peristalsis. PheWAS identified pleiotropic associations with dysmotility syndromes and the response to their pharmacological treatment. The genetic architecture of stool frequency correlates with that of IBS, and UK Biobank participants from the top 1% of stool frequency polygenic score distribution were associated with 5× higher risk of IBS with diarrhea. These findings pave the way for the identification of actionable pathological mechanisms in IBS and the dysmotility syndromes.